Ca2+ Signalling in Endothelial Progenitor Cells: A Novel Means to Improve Cell-Based Therapy and Impair Tumour Vascularisation - Moccia, Francesco; Lodola, Francesco; Dragoni, Silvia; Bonetti, Elisa; Bottino, Cinzia; Guerra, Germano; Laforenza, Umberto; Rosti, Vittorio; Tanzi, Franco (Current Vascular Pharmacology, 2014)
Endothelial progenitor cells (EPCs) have recently been employed in cell-based therapy (CBT) to promote regeneration of ischemic organs, such as heart and limbs. Furthermore, EPCs may sustain tumour vascularisation and provide an additional target for anticancer therapies. CBT is limited by the paucity of cells harvested from peripheral blood and suffers from several pitfalls, including the low rate of engrafted EPCs, whereas classic antiangiogenic treatments manifest a number of side effects and may induce resistance into the patients. CBT will benefit of a better understanding of the signal transduction pathway(s) which drive(s) EPC proliferation, trafficking, and incorporation into injured tissues. At the same time, this information might outline alternative molecular targets to impair tumor neovascularisation and improve the therapeutic outcome of antiangiogenic strategies. An increase in intracellular Ca2+ concentration is the key signal in the regulation of cellular replication, migration, and differentiation. In particular, Ca2+ signalling may regulate cellcycle progression, due to the Ca2+-sensitivity of a number of cycline-dependent kinases, and gene expression, owing to the Ca2+-dependence of several transcription factors. Recent work has outlined the role of the so-called store-operated Ca2+ entry in driving EPC proliferation and migration. Unravelling the mechanisms guiding EPC engraftment into neovessels might supply the biological bases required to improve CBT and anticancer treatments. For example, genetic manipulation of the Ca2+ signalling machinery could provide a novel approach to increase the extent of limb regeneration or preventing tumour vascularisation by EPCs.
Keywords: Endothelial progenitor cells